Role of Regional Financial & Assets Management Agency (BPKAD) in the Mediation Process of BPHTB & PPH - Siti Putri Indah Meilani (Sultan Agung Notary Law Review, 2021)
The research "The Role of the Regional Financial and Asset Management Agency (BPKAD) in the Mediation Process for Determining the Fee for Land and Building Rights/Income Tax (BPHTB/PPH) in Pati Regency" is motivated by myths that develop in the community regarding land ownership rights. This study aims to: 1) identify and analyze the role of BPKAD in Pati Regency. 2) knowing and analyzing the mediation process for determining BPHTB/PPH in Pati Regency. The research method in this thesis uses a sociological juridical approach with descriptive analysis specifications, namely data collection methods to obtain data that will be used as thesis material through interviews by conducting interviews with BPKAD Pati Regency, or by observation in the form of observations involved systematically in obtaining data. After that, qualitative analysis of the data obtained from various sources will be carried out. The results of the study indicate that: 1) BPKAD has not carried out its functions and roles as public servants properly. 2) The mediation process will be carried out between the seller and the buyer and BPKAD as the mediator.